Business communication in function of improving the organizational culture of the company - Sashko Gramatnikovski; Aleksandra Stoilkovska; Gordana Serafimovic (UTMS Journal of Economics, 2015)
This paper presents an action research conducted in function of proving the connection between effective communication and organizational culture. Bearing in mind that we communicate daily wherever we are, including our work places, we can conclude that communication is a part of our daily behavior. It is precisely our daily behavior that shows us our habits, norms, standpoints and value systems; the ones we have accepted and through which we manifest our behavior. Recognizing organizational culture within these frames is the challenge that this paper has taken on and it presents a successful attempt of proving the connection between business communication and organizational culture. The research has been conducted with a total of 282 examinees from the first ten of the top 200 organizations for 2013 in the Republic of Macedonia. The same has proven the general hypothesis about the connection between business communication and organizational culture.
Keywords: L20; 330; business communication; organizational culture; feedback information; effective listening; verbal communication